Analisis Penerapan Segmenting, Targeting, dan Positioning dalam Kesuksesan Usaha pada Bisnis Franchise Pocong Pancong - Mumtaza Rifda Maulidiyah; Ety Dwi Susanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
One major factor that contributes to a business enterprise's success is often the result of really poor market performance. Due to this persaingan, every business owner must take action to strengthen the business that is currently being conducted by implementing a few strategies such as segmentation, targeting, and positioning. These strategies were implemented by the Pocong Pancong franchise, and as of right now, they can be applied to most types of business persaingan. The purpose of this study is to analyze the Segmenting, Targetting, and Positioning that have been carried out by the Pocong Pancong franchise using a deskriptif qualitative research method with data collection by observation, interviews, and documentation. The types and summaries of data that are used combine primary and secondary data, resulting in a profit margin in this business that focuses on behavioral segmentation.The objective that is being pursued is to use product specialization as a means of product development and market segmentation as a means of product development strategy. When positioning products, Pocong Pancong franchises do so based on price and quality, where products with higher quality than their category competitors are offered at a higher price. Due to this, the strategies of segmentation, targeting, and positioning that the Pocong Pancong franchise has implemented in order to achieve the necessary success can be emphasized.